Designing electronic graphic symbol-based AAC systems: a scoping review. Part 1: system description. - Tönsing, Kerstin M.; Bartram, Jessica; Morwane, Refilwe E.; Waller, Annalu (Disability & Rehabilitation: Assistive Technology, 2024)
This is the first of two papers summarizing studies reporting on the design of electronic graphic symbol-based augmentative and alternative communication (AAC) systems, to determine the state of the field. The aim of this paper was to provide an overview of the general characteristics of the studies and to describe the features of the systems designed. A scoping review was conducted. A multifaceted search resulted in the identification of 28 studies meeting the selection criteria. Data were extracted relating to four areas of interest, namely (1) the general characteristics of the studies, (2) features of the systems designed, (3) availability of the systems to the public, and (4) the design processes followed. In this paper, findings relating to the first three areas are presented. Most study authors were affiliated to fields of engineering and/or computer science and came from high-income countries. Most studies reported the design of AAC applications loaded onto mobile technology devices. Common system features included customizable vocabulary items, the inclusion of graphic symbols from both established AAC libraries and other sources, a dynamic grid display, and the inclusion of digital and/or synthetic speech output. Few systems were available to the public. Limited justifications for many of the complex design decisions were provided in the studies, possibly due to limited involvement of rehabilitation professionals during the design process. Furthermore, few studies reported on the design of graphic symbol-based AAC systems specifically for middle- and low-income contexts and also for multilingual populations. Complex design decisions about electronic graphic symbol-based augmentative and alternative communication (AAC) systems should be made purposefully and with sufficient justification. Increased collaboration between designers and rehabilitation professionals during the design of electronic graphic symbol-based systems could improve the products. Design of AAC systems for populations residing in low and middle-income contexts and also for multilingual populations are urgently needed.